2012
DOI: 10.1142/s0217732312500149
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Anisotropy Due to Pre-Inflationary Phase of Cosmic Evolution

Abstract: We show that perturbations generated during the anisotropic preinflationary stage of cosmic evolution may affect cosmological observations today for a certain range of parameters. Due to the anisotropic nature of the universe during such early times, it might explain some of the observed signals of large scale anisotropy. In particular we argue that the alignment of CMB quadrupole and octopole may be explained by the Sachs-Wolfe effect due to the large scale anisotropic modes from very early times of cosmologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…An interesting possibility is that there might have been a phase of anisotropic expansion at very early time. The inflationary Big Bang cosmology is perfectly consistent with such an evolution [52]. The anisotropic modes, generated during this early phase may later re-enter the horizon [52,53] and lead to the observed signals.…”
Section: Introductionsupporting
confidence: 63%
“…An interesting possibility is that there might have been a phase of anisotropic expansion at very early time. The inflationary Big Bang cosmology is perfectly consistent with such an evolution [52]. The anisotropic modes, generated during this early phase may later re-enter the horizon [52,53] and lead to the observed signals.…”
Section: Introductionsupporting
confidence: 63%
“…There are several non-conventional explanation for the NVSS dipole. For example, the anisotropic mode generated before inflation may re-enter the horizon at late time and produce large scale anisotropy [48][49][50]. Alternatively, the primordial non-Gaussianities (NG) may affect the structures at large scales.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It has been shown that, for a wide class of models, there exists a parameter range such that the modes generated during this early phase can re-enter the horizon much before the current era and hence can affect present observations. 18 These can, in principle, generate the observed anisotropies.…”
Section: Introductionmentioning
confidence: 98%